FUNGSI BAHASA MANTRA PADA TRADISI PACU JALUR DI KABUPATEN KUANTAN SINGINGI: KAJIAN ANTROPOLINGUISTIK - Leny Syafyahya, Desti Marlina, Fajri Usman, (Universitas Andalas, 2023)
This study aims to describe the function of mantra language used in the pacu jalur tradition in Kuantan Singingi Regency. The research was conducted using anthropolinguistic approach. The method used is the method of involved observation with the basic techniques of participatory observation and interview techniques with the lane shaman in Pulau Rumput Village. Data in the form of mantras in the form of rhymes and poems. The results concluded that there are 3 informational functions, 4 directive functions, 2 expressive functions, and 3 aesthetic functions found in the mantra language in the pacu jalur tradition in Kuantan Singingi Regency.